Pengaruh Motivasi dan Komunikasi Terhadap Kinerja Karyawan PT. Astra Credit Companies (ACC) - Santi Dwi Yulisti; Kurnia Kurnia (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2022)
The purpose of this study was to determine partially or simultaneously the independent variables of motivation and communication on the performance of employees of PT. Astra Credit Companies, and to find out which of the two variables has a dominant effect on the dependent variable. This research uses quantitative methods, a population of 65 employees and samples taken from the entire population. Data obtained from the process of interviews, observations, and distributing questionnaires to respondents, the data were analyzed using multiple linear regression analysis to answer the hypothesis.The results of this study are: (1) motivational variables and have a positive and significant effect on employee performance with a significant level of 0.006 < 0.05; (2) the communication variable has a positive and significant effect on employee performance with a significant level of 0.019 < 0.05; (3) the variables of motivation and communcation have a positive and significant effect simultaneously on employee performance; Keywords : Motivation, Communication, Performance